Shape invariant modelling pricing kernels and risk aversion - Maria Grith; Wolfgang Karl Härdle; Juhyun Park (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
Pricing kernels play a major role in quantifying risk aversion and investors' preferences. Several empirical studies reported that pricing kernels exhibit a common pattern across different markets. Mostly visual inspection and occasionally numerically summarise are used to make comparison. With increasing amount of information updated every day, the empirical pricing kernels can be viewed as an object evolving over time. We propose a systematic modelling approach to describing the evolution of the empirical pricing kernels. The approach is based on shape invariant models. It captures the common features contained in the shape of the functions and at the same time characterises the variability between the pricing kernels based on a few interpretable parameters. The method is demonstrated with the European options and returns values of DAX index.
Keywords: C14; C32; G12; 330; Pricing kernels; risk aversion; risk neutral density; Börsenkurs; Core; Index-Futures; Anlageverhalten; Risikoaversion; Theorie; Europa